The Influence of HR Competence and Work Discipline on Employee Performance at the Soromandi Sub-District Office of Bima Regency - Yuyun saputri; Ikbal Irawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Research Objectives 1. To determine the competence of human resources has a partial effect on the performance of employees at the Soromandi sub-district office, Bima Regency. 2. To determine that work discipline has a partial effect on employee performance at the Soromandi sub-district office of Bima Regency.3. To determine the competence of human resources and work discipline have a simultaneous effect on the performance of employees at the Soromandi sub-district office of Bima Regency. The type of research used is associative research, which is research that aims to determine the relationship between two or more variables (Sugiyono: 2014: 44) data analysis, Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Test, t-statistical test, Determination Test, Multiple Correlation Coefficient. Based on the results of data analysis that has been carried out, it can be concluded between: 1). HR competence does not have a partial effect on employee performance at the Soromandi sub-district office, Bima Regency, 2). There is an influence of work discipline simultaneously affecting employee performance at the Soromandi sub-district office of Bima regency 3). HR competence and work discipline simultaneously affect employee performance at the Soromandi sub-district office in Bima Regency